Analisis Kebijakan Stimulus Fiskal dan Moneter untuk Pembangunan Komoditi Kelapa Sawit Indonesia - -, Suharyadi (Jurnal Aplikasi Manajemen, 2009)
Financial crisis which leads to global economic downturn have stimulated the occurrence of food crisis in the early of 2008; spurred rice and CPO price for rising between 200-300%, and later on decreasing until 100% in the early of 2009. This phenomenon have being an important indicators for the Indonesia’s government to pay more attentions toward primary sector or agriculture and food endurance to guard national stability, aside from industrial needs and renewable energies. The role of plantation sector and palm-oil become more important due to energy crisis, because of those sectors are being one of alternative energy resources in the midst of global oil crisis, Middle East crisis and Indonesia as the second largest palm-oil producers in the world. This research focused on appropriate fiscal and monetary policy to boost palm-oil industries growth; that are comprised by export-tax policy, interest, currency exchange and retribution. The research found that export, production, and oil-palm productivities are considerably respond to export-tax policy, interest and price. The fierce competition with Malaysia’s producers could influence export price and as the consequence, would lowering the terrain and productivity of Indonesia’s palm-oil. Mutualism cooperation should be build in order to create a synergic and symbiotic collaboration in the market which could be benefit for both world biggest palm oil producers. Fiscal stimulus policies that will be applied by the government that will become very relevant based on this research are tax and interest factor.Keywords: plantation sector, palm-oil, export, consumption, fiscal and monetary policy